Refractory electrical storm in coronary artery disease patient, challenges of dying heart - Rafid Fayadh Al-Aqeedi; Goma Mauuf; Eiman Nabi (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
Electrical storm most often occurs in patients with coronary artery disease and left ventricular dysfunction. We report a case of recurrent ventricular Tachycardia (VT) in a 49-year-old male patient previously known to have an inferior myocardial infarction and hypertension, presented with ischemic chest pain accompanied by dizziness, hypotension, and tachycardia. An electrocardiogram showed monomorphic VT. A prompt synchronized electrical cardioversion under sedation has reverted the rhythm to the sinus. An echocardiogram showed left ventricular segmental wall motion abnormalities and ejection fraction of 37%. Then the condition complicated by recurrent VT necessitates multiple electrical cardioversions and defibrillation given for recurrent ventricular Fibrillation (VF) and short cardiopulmonary resuscitations that revived the patient from cardiac arrests. The patient had received a total of 103 electrical shocks over 15 days during which, he developed circulatory and respiratory compromise that required mechanical ventilation on twice occasions. Meticulous care including central monitoring and inotrope for hypotensive episodes was provided. A coronary angiogram showed normal left anterior descending and circumflex coronary arteries and a totally occluded right coronary artery which was failed to be revascularized in an attempt of angioplasty. The patient was successfully weaned off the ventilator and run a quiet course afterward. An implantable cardioverter-defibrillator was placed while maintained on oral amiodarone, mexiletine, metoprolol, and omega-3-acid ethyl esters, then discharged asymptomatic without recorded dysrhythmias. This case report underscores the challenges encountered throughout the management of such particular life-threatening ventricular arrhythmias and their impact on patient safety.